Odpowiedzi

Najlepsza Odpowiedź!
2010-01-12T17:30:25+01:00
3x - 2y = -12 /∙ (-2)
2x - 5y = -19 /∙ 3

-6x + 4y = 24
6x - 15y = -57
+______________
-11y = -33 /: (-11)
y = 3

3x - 2 ∙ 3 = -12
3x - 6 = -12
3x = -6 /: 3
x = -2

x = -2
y = 3



3x + 2y = 13
2x + y = 11

3x + 2y = 13
y = 11 - 2x

3x + 2(11 - 2x) = 13
3x + 22 - 4x = 13
3x - 4x = 13 - 22
-x = -9 /: (-1)
x = 9

2 ∙ 9 + y = 11
18 + y = 11
y = -7

x = 9
y = -7
2010-01-12T17:34:08+01:00
1)
{3x -2y = -12
{2x- 5y = -19

{3x=2y-12
{2x- 5y = -19

{x = 2/3 y -4
{2x- 5y = -19

2(2/3 y -4) -5y= -19
4/3y - 8 -5y= -19
-11/3 y = -11
y= 3

x= 2/3 * 3 -4
x= -2


2)
{3x+ 2y = 13
{2x + y = 11

{3x+ 2y = 13
{x= 5,5 -0,5y

3(5,5 -0,5y) +2y =13
16,5 - 1,5y +2y =13
0,5y= -3,5
y= -7

x=5,5 +3,5
x=9